FAKTOR-FAKTOR YANG MEMPENGARUHI FINANCIAL STATEMENT FRAUD DALAM PERSFEKTIF FRAUD TRIANGLE PADA ORGANISASI PERANGKAT DAERAH KABUPATEN KAMPAR (Studi Empiris Pada OPD Kabupaten Kampar Tahun 2018) - Hasanah, Wirdatul; Basri, Yesi Mutia; Desmiyawati, Desmiyawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This study aims to explore the perceptions of government officials in Kampar regency government about the tendency of fraud in the government sector and the factors that influence it. In this study the factors used that can effect the occurrence of fraud are the factors of law enforcement, the effectiveness of Internal control system, leadership style, compensation suitability and organizational commitment. Population In this study is the organization of regional devices (OPD) contained in Kampar district. while the sample set by researchers In this study is the OPD in Kampar district as many as 30 OPD. sampling technique using purposive sampling. data collection is done by using questionnaire method. each OPD will be distributed as many as 5 questionnaires addressed to the Head of the Office, PPTK, financial sub-head, head of finance and treasurer of the financial section of each OPD in Kampar district so the number of respondents In this study were as many as 150 respondents. method of data analysis used is method of multiple regression analysis through software software SPSS 21,0 msi. The results of this study can be concluded that law enforcement, system effectiveness Internal control, leadership style, compensation suitability and organizational commitment have a significant negative effect on the tendency of fraud in the organization of Kampar district area.Keywords : Factors Affecting Financial Statement Fraud In Fraud Triangle Perspective.